LINGUACULTURAL FEATURES OF UZBEK PROVERBS AND THEIR ROLE IN LANGUAGE AND CULTURE - Xakimjonova Oltinoy,; Panjiyeva Ruxsora Dilmurodovna, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Language and culture are closely linked. This connection is clear in proverbs. Proverbs reveal the traditions, values, and worldview of a society. The goal of this article is to explore the features of Uzbek proverbs and their significance in language and communication. We will focus on the meanings of proverbs and how they reflect the national mentality and moral values of the Uzbek people. Uzbek proverbs often share wisdom, life experiences, and social norms that have been passed down through generations. We will also compare some Uzbek proverbs with expressions in English to highlight both universal and culture-specific aspects of proverbial language. The results will show that proverbs are not just linguistic units; they are also important cultural markers that preserve collective knowledge and identity. Understanding proverbs can improve language learning and intercultural communication.